1986
DOI: 10.1113/jphysiol.1986.sp016016
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐gated potassium conductance in human T lymphocytes stimulated with phorbol ester.

Abstract: SUMMARY1. The whole-cell patch-clamp method was used to study the voltage-gated K+ conductance of human peripheral blood T lymphocytes.2. After entry into whole-cell recording mode, there are time-dependent changes in some properties of the conductance. Over the first 10-30 min, the threshold for activation shifts about 10 mV more negative, and the rates of activation and inactivation increase. Inactivation is less strongly voltage dependent than activation or deactivation.3. Lymphocytes were stimulated to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 51 publications
6
111
0
Order By: Relevance
“…Dupuis et al (1989) have, in addition, found that in cells displaying a PHA-sensitive Ca2+ current, IK(V) was inhibited probably by an increase in internal Ca2+. Bregestovski, Redkozubov & Alexeev (1986) demonstrated that IK(V) is inhibited by intracellular Ca2+ and this relationship may account for the failure of other groups to detect any reproducible effect on IK(V) in human T-cells by PHA or phorbol esters (Deutsch, Krause & Lee, 1986;Schlichter, Sidell & Hagiwara, 1986b). Our patchclamp studies showed a low density of voltage-gated K+ channels in resting rat thymocytes and no activation of this class of K+ channels by ConA.…”
Section: Discussionmentioning
confidence: 80%
“…Dupuis et al (1989) have, in addition, found that in cells displaying a PHA-sensitive Ca2+ current, IK(V) was inhibited probably by an increase in internal Ca2+. Bregestovski, Redkozubov & Alexeev (1986) demonstrated that IK(V) is inhibited by intracellular Ca2+ and this relationship may account for the failure of other groups to detect any reproducible effect on IK(V) in human T-cells by PHA or phorbol esters (Deutsch, Krause & Lee, 1986;Schlichter, Sidell & Hagiwara, 1986b). Our patchclamp studies showed a low density of voltage-gated K+ channels in resting rat thymocytes and no activation of this class of K+ channels by ConA.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, in T lymphocytes, which express Kv␤ proteins (15), Kv1.3 inactivates with a time constant of 150 -200 ms at ϩ40mV (37), similar to that in LPS-stimulated BMDM. However, this could be as a result of the model because human T cells were activated with PHA A to increase K ϩ channel expression (37,38). Thus, Kv1.3 in BMDM and T cells inactivates faster than in HEK cells, suggesting a role for Kv␤ subunits in the leukocyte membrane excitability.…”
Section: Discussionmentioning
confidence: 97%
“…In human T cells, the number of type n K(V) channels per cell increases, but the density of these channels probably remains about the same; in our experiments using T cells activated for 3-6 d, we found a 3.4-fold increase in gK00 compared with resting cells, an increase that paralleled the increase in surface area of cells selected for patch clamping in the population. Deutsch and colleagues found an increase in gK~v) of 1.7-fold for 1-and 2-d PHA-activated T ceils after mitogenic activation (Deutsch, Krause, and Lee, 1986). In mouse T cells, a relatively larger increase in the number of K(V) channels after mitogenic activation represents an increase in the density of K(V) channels; the number of these channels in resting murine T cells is lower than in resting human T cells (DeCoursey, Chandy, Gupta, and Cahalan, 1987b).…”
Section: Changes In Channel Expression That Precede Cell Divisionmentioning
confidence: 99%